Diversity Identification of Home Industry of Shrimp Paste Product in Banten Province - Sakinah Haryati; Aris Munandar (Jurnal Perikanan dan Kelautan, 2011)
The shrimp paste products is one of the traditionally processed products by fermentation. Shrimp paste products are familiar in every layer of society in Indonesia, which is commonly used as a flavoring dishes. A study to identify the diversity of shrimp paste products have been carried to know the home industry diversity of shrimp paste products, in Banten province as well asits physical quality. The shrimp paste products diversity was observed in the market directly and also by interview with the producer in Banten Province. The identification of shrimp paste product was conducted with physical test of filth, that was the foreign materials that mixed-up with raw shrimp paste products. The results showed that there were different raw materials used as well as the product forms, processing, physical quality of the product, pricing and marketing distribution of the shrimp paste products. Almost-uniform product of shrimp paste were found between Pandeglang (TP) and Serang (TS) shrimp paste product, while that of Domas (TD) and Binuangeun (TB) were relatively same in its diversity. Domas (TD) and Binuangeun (TB) shrimp paste product were of good quality, made of terasi shrimp, without dyes additive, and fillers. While that of Pandeglang (TP) and Serang (TS) were of low quality due to the use of waste of salted fish, dyes, and filler material.